Impact of low/no-charge coronary artery calcium scoring on statin eligibility and outcomes in women: The CLARIFY study - Sadeer Al-Kindi; Nour Tashtish; Imran Rashid; Claire Sullivan; Ian J Neeland; Monique Robinson; Ewa M. Gross; Leslee Shaw; Miguel Cainzos-Achirica; Khurram Nasir; Catherine Kreatsoulas; Robert Gilkeson; et al. (Elsevier, 2022)
Background: Prior studies have suggested significant underutilization of statins in women and worse cardiovascular outcomes. Data examining the impact of real-world coronary artery calcium (CAC) scoring to improve utilization of preventive therapies and outcomes is limited. Methods: In a prospective registry study of low cost or no-cost CAC scoring between 2014 and 19 (CLARIFY Study, Clinicaltrials.gov NCT04075162), we sought to study the association of CAC scoring on statin utilization, blood lipids (LDL, total cholesterol, triglycerides), downstream ischemic testing (coronary angiography and stress testing), coronary revascularization and outcomes (MI, stroke, death) in women compared with men. Eligibility for statin initiation was defined as atherosclerotic cardiovascular disease pooled cohort equation (ASCVD-PCE) ≥ 7.5% and CAC≥100/≥75th percentile. Results: A total of 52,151 patients (26,336 women and 25,815 men) were enrolled. Women were more likely to have CAC 0 (51% vs 30%, P<0.001). Among patients not eligible for statin by PCE, CAC reclassified statin eligibility in a smaller proportion of women than men (25.4% vs 30%, P<0.001), while among patients eligible for statin by PCE, CAC was more likely to downgrade risk/statin eligibility in women than men (30.1% vs 48.4%, P<0.001). After CAC scoring, statin initiation was similar in women and men, but high-intensity statin use was lower in women (CAC-adjusted HR 0.76 [0.70-0.83], P<0.001). Women had similar reduction in LDL cholesterol levels compared with men. There was no difference between men and women with respect to CAC-stratified major adverse cardiovascular events. Conclusion: CAC scoring primarily served to downgrade statin eligibility in women compared with men. Women had similar CAC risk-guided reductions in LDL cholesterol compared with men.